Regularização de territórios quilombolas: discursos de representação em análise - BRASIL, Rosangela Lima (2018)
This work analyzes constructions of representation discourses in contexts involving processes of regularization of quilombola territories. The policy of regularization of quilombolas territories, in charge of the National Institute for Colonization and Agrarian Reform (INCRA) since 2003, complies with the provisions of article 68 of the ADCT, of the Federal Constitution of 1988, which recognizes the remnants of quilombos ", who occupy their lands, the definitive property and grants them respective titles. For an up-to date approach of this subject of collective rights, anthropologists have proposed resemantizing the term "remnants of quilombos communities", deconstructing old and essentialist notions present in the popular imaginary. Mobilized around the new category, innumerable black communities, now organized, started to claim from the State the titling of their territories and other actions in the areas of infrastructure, education, health and culture. As the definition resemantized by anthropologists, the State itself constructs its own definition of "remnants of quilombos communities", which serves as a reference to institutional processes of recognition. The analyzes presented in this dissertation aim to identify the main symbolic elements triggered in legal texts and the way they are mobilized in the construction of this referential of institutionalized representation. They also seek to understand which elements are triggered and mobilized in representational discourses, in contexts of disputes for the power of representation, in processes of regularization of quilombola territories. The analyzes focus on legal texts, technical reports of territorial identification and socio-historical characterization and speeches of representations that could not be legitimized along the regularization process, in processes that are under way in Maranhão. For that, I mobilize principles of Michel Foucault's discursive analysis (1999) and adopt some concepts about culture, language and representation of authors such as Stuart Hall (1997, 2003, 2006, 2016), Bourdieu (1983, 2000, 2001) and Jandira Butler (2003, 2014).